prophylactic intramuscular ephedrine in elective caesarean section under bupivacaine spinal anaesthesia. - Mayakesavan, Prabhu (2002)
ABSTRACT: Objective: This study was carried out the objective of assessing the safety and efficacy of 30 mg intramuscular in preventing hypotension associated with spinal anaesthesia for elective Caesarean section. Method: in a double-blind randomized controlled study 40 patients(20 in each group) were given either 30mg 90.6ml) ephedrine or an equal volume of normal saline. The following parameters were recorded: I. Systolic blood pressure II. Heart rate III. Oxygen saturation IV. ECG V. Rescue ephedrine iv supplementation. Results: The incidence of hypotension was lower in the ephedrine group950%) as compared to the saline group(8050, but this difference was not statistically significant. However, the incidence of delayed hypotension was significantly different between two groups, with and incidence of only 5% in the ephedrine group as compared with 60% in the saline group (p< 0.05). There was no incidence of hypotension or tachycardia in either group. There was no difference in mean highest systolic blood pressure or mean highest heart between the two groups. Conclusion: Hence, this study showed that giving 30mg ephedrine intramuscularly immediately after spinal anaesthesia was not associated with hypertension was seen in patients receiving prophylactic intramuscular ephedrine.